MicroRNA Sequence Variation Potentially Contributes to Within-Species Functional Divergence in the Nematode Caenorhabditis briggsae - Jovelin, Richard (Genetics Society of America, 2011)
Mounting evidence points to differences in gene regulation as a major source of phenotypic variation. MicroRNA-mediated post-transcriptional regulation has emerged recently as a key factor controlling gene activity during development. MicroRNA genes are abundant in genomes, acting as managers of gene expression by directing translational repression. Thus, understanding the role of microRNA sequence variation within populations is essential for fully dissecting the origin and maintenance of phenotypic diversity in nature. In this study, we investigate allelic variation at microRNA loci in the nematode Caenorhabditis briggsae, a close relative of C. elegans. Phylogeographic structure in C. briggsae partitions most strains from around the globe into a “temperate” or a “tropical” clade, with a few strains having divergent, geographically restricted genotypes. Remarkably, strains that follow this latitudinal dichotomy also differ in temperature-associated fitness. With this phylogeographic pattern in mind, we examined polymorphisms in 18 miRNAs in a global sample of C. briggsae isolates and tested whether newly isolated strains conform to this phylogeography. Surprisingly, nucleotide diversity is relatively high in this class of gene that generally experiences strong purifying selection. In particular, we find that miRNAs in C. briggsae are substantially more polymorphic than in Arabidopsis thaliana, despite similar background levels of neutral site diversity between the two species. We find that some mutations suggest functional divergence on the basis of requirements for target site recognition and computational prediction of the effects of the polymorphisms on RNA folding. These findings demonstrate the potential for miRNA polymorphisms to contribute to phenotypic variation within a species. Sequences were deposited in GenBank under accession nos. JN251323–JN251744.